Advances in the surgical treatment of hilar cholangiocarcinoma. (March 2015) - Tsuchikawa, Takahiro; Hirano, Satoshi; Okamura, Keisuke; Matsumoto, Joe; Tamoto, Eiji; Murakami, Soichi; Nakamura, Toru; Ebihara, Yuma; Kurashima, Yo; Shichinohe, Toshiaki
<x xml:space="preserve">Abstract</x> With the improvement of perioperative management and surgical techniques as well as the accumulation of knowledge on the oncobiological behavior of bile duct carcinoma, the long-term prognosis of hilar cholangiocarcinoma has been improving. In this article, the authors review the recent developments in surgical strategies for hilar cholangiocarcinoma, focusing on diagnosis for characteristic disease extension, perioperative management to reduce postoperative morbidity and mortality, surgical techniques for extended curative resection and postoperative adjuvant therapy.